2004
DOI: 10.1210/jc.2003-031144
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Lipolysis and Salivary Cortisol to Food Intake and Physical Activity in Lean and Obese Children

Abstract: This investigation was conducted to determine whether there were differences in lipolytic responses to feeding and physical activity between lean (LN) and obese (OB) children, and if these responses were related to cortisol. Fourteen LN and 11 OB children participated in this study of abdominal lipolysis and salivary cortisol response to breakfast and lunch with an intervening exercise session. Calculated fasting glycerol release was lower in OB than LN (0.645 +/- 0.06 vs. 0.942 +/- 0.11 micromol/ml; P < 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
3
17
0
1
Order By: Relevance
“…Although this concurs with previous research (Lac and Berthon 2000;Dimitriou et al 2002;McGuigan et al 2004;Di Luigi et al 2006), there have been exceptions in the literature (Sills and Cerny 1983;Ben-Aryeh et al 1989;Hershberger et al 2004). Normally, exercise would be expected to increase cortisol levels (Dimitriou et al 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Although this concurs with previous research (Lac and Berthon 2000;Dimitriou et al 2002;McGuigan et al 2004;Di Luigi et al 2006), there have been exceptions in the literature (Sills and Cerny 1983;Ben-Aryeh et al 1989;Hershberger et al 2004). Normally, exercise would be expected to increase cortisol levels (Dimitriou et al 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with those by Sari-Sarraf et al (2007) who showed that a soccer-specific exercise is able to cause an increase in salivary cortisol when performed in the afternoon but not in the morning. Similarly, Hershberger et al (2004) have reported that a 26-min exercise session performed at 1230 hours was associated with no significant change in lean children, and with a significant decrease in obese children.…”
Section: Discussionmentioning
confidence: 93%
“…Time of awakening (Federenko et al 2004) and nocturnal awakening (Hucklebridge et al 2000), what is found frequently in pregnant women, may also affect salivary cortisol levels. Food intake (Hershberger et al 2004), caffeine (Lovallo et al 2005), and moderate physical activity (Frey 1982) may be physiological challenges to the HPA axis. Although most pregnant women stay abstinent from alcohol and nicotine, both can have pronounced effects on the endocrine function.…”
Section: Discussionmentioning
confidence: 99%